Brucella evolution and taxonomy - Cloeckaertb, Axel (2002)
The genus Brucella contains alpha-Proteobacteria adapted to intracellular life within cells of a variety of mammals. Controversy has arisen concerning Brucella internal taxonomy, and it has been proposed that the DNA–DNA hybridization-based genomospecies concept be applied to the genus. According to this view, only one species, Brucella melitensis, should be recognized, and the classical species should be considered as biovars (B. melitensis biovar melitensis; B. melitensis biovar abortus; etc.). However, a critical reappraisal of the species concept, a review of the population structure of bacteria and the analysis of Brucella genetic diversity by methods other than DNA–DNA hybridiza- tion show that there are no scientific grounds to apply the genomospecies concept to this genus. On the other hand, an enlarged biological species concept allows the definition of Brucella species that are consistent with molecular analyses and support the taxonomical standing of most classical species. Both the host range as a long-recognized biological criterion and the presence of species- specific markers in outer membrane protein genes and in other genes show that B. melitensis, B. abortus, B. ovis, B. canis and B. neotomae are not mere pathovars (or nomenspecies) but biologically meaningful species. The status of B. suis is, however, less clear. These approaches should be useful to define species for the marine mammal Brucella isolates, as illustrated by the grouping of the isolates from pinnipeds or from cetaceans by omp2 gene analysis. It is shown that a correct Brucella species definition is important to understand the evolution of the genus.